Addressing Pedagogical Challenges Faced by English Lecturers at Halabja University, Kurdistan: A Qualitative Study - Ghafar, Zanyar; Nabaz Nariman MOHAMMED; Ciptro HANDRIANTO; M. Arinal RAHMAN (RADINKA JAYA UTAMA PUBLISHER, 2024)
This study addresses the challenges faced by English lecturers at the College of Basic Education at Halabja University, Kurdistan, aiming to contribute insights that can inform improved regulations and enhance English Language Teaching (ELT) at the university. The data collected via semi-structured interviews was subjected to thematic analysis, and five English lecturers participated. The results of this study focus on the obstacles encountered by English instructors, exploring themes such as student motivation, language competence, class size, time constraints, and inadequate facilities. The study underscores the need for targeted interventions to address these challenges and improve the overall quality of ELT. Based on the findings, specific recommendations include implementing motivational strategies in the classroom, providing additional language support resources for students, reducing class sizes where possible, allowing more preparation time for lecturers, and upgrading classroom facilities and teaching materials. The findings highlight English lecturers' intricate issues, emphasize the necessity for institutional and governmental support to facilitate a more conducive teaching and learning environment, and reveal significant challenges, including students' lack of motivation, linguistic proficiency issues, difficulties managing large classes, time constraints, and insufficient teaching resources